Evaluation And Implementation Of Surveillance Systems During The Covid-19 Pandemic At The Padang Class II Port Health Office Working Area Of Minangkabau International Airport - Astuti, Yulia; Gusti, Aria; Magdalena, Magdalena (Green Publisher, 2021)
Covid-19 has been declared a global pandemic by the World Health Organization. In addition, it has been declared a national disaster by the President of Indonesia. One of the efforts to prevent disease entry in an area is through surveillance activities, one of which is carried out at the Port Health Office of the Minangkabau International Airport Working Area. This research used qualitative research with a case study approach which will be carried out in February-March 2021. Information is obtained from the Surveillance section of the BIM Wilker Port Health Office. The variable in this study is the surveillance system during the Covid-19 pandemic, surveillance management activities are carried out using a systems approach consisting of input, process, and output. The instruments used in this study were interviews, cameras, tape recorders, and writing instruments. Data analysis was carried out through gap analysis. In the implementation of the input, process, and output processes, it is necessary to add personnel and increase knowledge in the implementation of data processing, analysis, and interpretation to provide information to the public in a surveillance system. Conclusions from the field study in the implementation of the surveillance system during the Covid-19 Pandemic at BIM Padang have been running but have not met the surveillance system approach. Efforts should be made to disseminate information, socialize and provide human resources and training to improve the capacity of officers.